THE RELATIONSHIP BETWEEN NURSES’ CARING BEHAVIOR AND INPATIENT SATISFACTION LEVELS AT BHAYANGKARA HOSPITAL - Imran Rusdi; IGA Purnama Wulan (Yayasan Wayan Marwan Pulungan, 2026)
Nurses play a crucial role as the frontline providers of healthcare services, and their caring behavior is one of the essential aspects that determine the quality of nursing care. Caring not only reflects humanitarian values but also significantly influences patient satisfaction. This study aims to analyze the relationship between nurses’ caring behavior and the level of patient satisfaction among inpatients at Bhayangkara Brimob Hospital. The research employed a quantitative approach with a cross-sectional design. A total of 40 inpatients from wards on the 3rd and 5th floors were recruited using purposive sampling, based on predetermined inclusion criteria. Data were collected using validated and reliable questionnaires measuring nurses’ caring behavior and patient satisfaction. Data analysis was conducted using univariate and bivariate methods, with the Spearman Rank test applied to examine the relationship between variables. The findings revealed that most nurses demonstrated caring behavior at the “often” category (52.5%), while the majority of patients reported being “very satisfied” (58.97%) with the nursing services they received. Statistical analysis confirmed a significant relationship between caring behavior and patient satisfaction (p = 0.033). These results highlight that the better the quality of caring behavior demonstrated by nurses, the higher the level of patient satisfaction. Therefore, strengthening nurses’ caring competencies should be prioritized as part of efforts to improve the overall quality of nursing care services.